The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1192/apt.11.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication and breast-feeding

Abstract: The physical and psychological benefits of breastfeeding for the mother and the infant are numerous and range from improved and stronger bonding to better immunological protection. Breast-fed infants have fewer episodes of middle-ear and urinary tract infections and lower mortality rates than bottle-fed babies (Nulman et al, 2003). Breast milk contains nucleotides and enzymes that promote digestion and absorption of nutrients. Breast-feeding has been associated with better cognitive functioning and better perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
(40 reference statements)
0
7
0
1
Order By: Relevance
“…Schimmell et al . [29,30] studied drug plasma levels in a breast-fed infant whose mother had taken clomipramine during pregnancy and continued after giving birth. They found that levels were high following delivery but decreased gradually and were at the lowest detectable concentration at 35 days, even though breast-feeding continued.…”
Section: Discussionmentioning
confidence: 99%
“…Schimmell et al . [29,30] studied drug plasma levels in a breast-fed infant whose mother had taken clomipramine during pregnancy and continued after giving birth. They found that levels were high following delivery but decreased gradually and were at the lowest detectable concentration at 35 days, even though breast-feeding continued.…”
Section: Discussionmentioning
confidence: 99%
“…[48] Anti-psychotics Typical anti-psychotics have been reported to be safe during breast feeding. [49] Their levels in maternal milk and infant serum have been found to be low. Also, these have not been associated with any adverse effects in the infants.…”
Section: Anti-depressantsmentioning
confidence: 99%
“…Although there are no reports on adverse effects due to the use of olanzapine and risperidone by breast-feeding mothers, it has been recommended to consider the riskbenefit analysis before their prescription. [49] Reports have suggested that clozapine accumulates in breast milk and its use is contraindicated during breast feeding. [50] There is limited information on amisulpride and quetiapine to make any favorable recommendations for their use.…”
Section: Anti-depressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exception to this is fluoxetine, which appears to have a dose-related risk for detectable levels in infant sera. [86] …”
Section: Pregnancy and Lactationmentioning
confidence: 99%